187k views
5 votes
Can you solve this pls 5(x – 4) + 3x – 9x = 6 – (2x + 5) + 8x

show step by step pls

User Lilyan
by
4.7k points

1 Answer

3 votes

Answer: x= -3

Explanation:

Step 1: Simplify both sides of the equation.

5(x−4)+3x−9x=6−(2x+5)+8x

(5)(x)+(5)(−4)+3x+−9x=6+−2x+−5+8x(Distribute)

5x+−20+3x+−9x=6+−2x+−5+8x

(5x+3x+−9x)+(−20)=(−2x+8x)+(6+−5)(Combine Like Terms)

−x+−20=6x+1

−x−20=6x+1

Step 2: Subtract 6x from both sides.

−x−20−6x=6x+1−6x

−7x−20=1

Step 3: Add 20 to both sides.

−7x−20+20=1+20

−7x=21

Step 4: Divide both sides by -7.

−7x

−7

=

21

−7

x=−3

User Jean Rostan
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.